KELAYAKAN USAHATANI BAYAM (Amaranthus spp) MEDIA PASIR DESA ABUMBUN JAYA KECAMATAN SUNGAI TABUK KABUPATEN BANJAR - Fitri Mahyudi; Husinsyah Husinsyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
This Research aim to know technically about effort management spinach farming evaluated from technical aspect in Abumbun Jaya Village Sungai Tabuk Subdistrict  Banjarbaru City South Kalimantan Province  and to know  about cost, acceptance, revenue and spinach farming Feasibility.  Pursuant to result of seen from technical management spinach farming  still relative modestly, this seen from farm processing until the conservancy. Production obtained from 25 spinach farmer  responder with wide mean equal to 352.236,45kg/ farmer. Productivity 1.030,64kg. Total  Revenue with mean Rp. 5.668.520 per farmer. RCR Value spinach farming 1.67 competent so that to be feasible (RCR >1).